The gender responsiveness of social marketing interventions focused on neglected tropical diseases - Nathaly Aya Pastrana; Claire Somerville; L. Suzanne Suggs (Taylor & Francis Group, 2020)
Background: Gender is a determinant of health that intersects with other social stratifiers to shape the health and well-being of populations. Despite the recognition of gender in the global health agenda, limited evidence exists about the integration of gender considerations in interventions, including social marketing interventions, for the prevention and control of neglected tropical diseases. Social marketing is an ethical approach to behavior change aiming to benefit individuals, communities, and society. Since behaviors are gendered and affect disease transmission and healthcare patterns, one would expect social marketing interventions to be gender responsive. Objective: This study aims to understand the extent to which social marketing interventions focusing on neglected tropical diseases are gender responsive. Methods: This study uses data from social marketing interventions collected in a systematic review, this study examined 20 interventions addressing eight neglected tropical diseases in 13 countries. A modified version of the World Health Organization Gender Assessment Tool (GAT) was used to determine the gender responsiveness of the interventions, which was complemented by coding for intersectional sex and gender data. These results are presented in 12 themes. Results: One schistosomiasis intervention implemented in China was assessed as gender responsive. It was not possible to answer many questions from the GAT due to limited data reported in the publications describing the interventions. Despite this, strengths and limitations were found in all the interventions in relation to the use of sex and gender concepts, the disaggregation of data, the consideration of environmental factors, and the involvement of women or men in the different stages of the interventions. Conclusions: Many interventions showed positive actions towards gender responsiveness. However, only one was classified as gender responsive. Others failed to supply enough data for assessment. Recommendations about how sex and gender could be integrated into social marketing interventions are provided.